2018
DOI: 10.1021/acs.inorgchem.8b02299
|View full text |Cite
|
Sign up to set email alerts
|

Strong Influence of Ancillary Ligands Containing Benzothiazole or Benzimidazole Rings on Cytotoxicity and Photoactivation of Ru(II) Arene Complexes

Abstract: A new family of neutral ruthenium(II) arene complexes of the type [Ru(η 6 -arene)X(κ 2 -O,N-L)] (η 6 -arene = p-cym, bz; X = Cl − , SCN − ; HL1 = 2-(2′-hydroxyphenyl)benzimidazole, HL2 = 2-(2′hydroxyphenyl)benzothiazole) has been synthesized and characterized. The cytotoxic activity of the Ru(II) complexes was evaluated in several tumor cell lines (A549, HepG2 and SW480) both in the dark and after soft irradiation with UV and blue light. None of the complexes bearing benzimidazole (HL1) as a ligand displayed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…The neutral chloride complexes I and II of general formula [( p -cym)­Ru­(Cl)­(κ 2 - O^N–L)] ( p -cym = p -cymene; L = L1, L2) previously prepared by us were found to be useful precursors for the synthesis of the new cationic complexes depicted in Scheme . Thus, chloride replacement by the imidazole derivatives MeIm ( N -methylimidazole) and EpipIm (N-ethylpiperidylimidazole) in the presence of a sodium salt (NaCl, NaBF 4 or NaBPh 4 ) yielded [( p -cym)­Ru­(κ 2 -O^N–L)­(MeIm)] + (L = L1 ([ 1 ] + ), L2 ([ 2 ] + )), and [( p -cym)­Ru­(κ 2 -O^N–L1)­(EpipIm)] + ([ 6 ] + ), which were isolated as the corresponding Cl – , BF 4 – , and BPh 4 – salts.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The neutral chloride complexes I and II of general formula [( p -cym)­Ru­(Cl)­(κ 2 - O^N–L)] ( p -cym = p -cymene; L = L1, L2) previously prepared by us were found to be useful precursors for the synthesis of the new cationic complexes depicted in Scheme . Thus, chloride replacement by the imidazole derivatives MeIm ( N -methylimidazole) and EpipIm (N-ethylpiperidylimidazole) in the presence of a sodium salt (NaCl, NaBF 4 or NaBPh 4 ) yielded [( p -cym)­Ru­(κ 2 -O^N–L)­(MeIm)] + (L = L1 ([ 1 ] + ), L2 ([ 2 ] + )), and [( p -cym)­Ru­(κ 2 -O^N–L1)­(EpipIm)] + ([ 6 ] + ), which were isolated as the corresponding Cl – , BF 4 – , and BPh 4 – salts.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The coordination bond distances lie in the expected range (close to 2 Å). , The Ru–O (2.066–2.081 Å) and Ru–N bond distances (2.068–2.111 Å) of the chelate ligands are very similar in the different complexes with a longer distance for the Ru–N­(benzothiazolyl) bond (complex [ 3 ]­BF 4 ), as has been previously observed in II (see Scheme ). The Ru–N­(RIm) distance (2.100–2.106 Å) is similar to those in related complexes reported in the literature. , The Ru–C­(average) and Ru–C­(centroid) distances are very similar in the four complexes and are also standard. , The bite angle N1–Ru–O1 is slightly higher for the complex with O^N–L2 (84.02(7) °) than for complexes with the O^N–L1 ligand (82.1–82.9°).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…García et al investigated a neutral Ru(II) arene complex 73 bearing a benzothiazole ligand (HL2) as the bidentate ligand [ 132 ]. The results of this study indicated that the arene ligand is released after irradiation with UV light even in the absence of oxygen and leads to cytotoxicity enhancement, thus revealing the potential of 73 as a prodrug for PACT.…”
Section: Ruthenium(ii) Arene Complexesmentioning
confidence: 99%
“…Especially their anticancer activities have received a great deal of attention. [1][2][3][4][5][6][7][8][9] On the other hand, arene ruthenium(II) complexes have been also applied to synthetic studies as a sort of building block for constructing a series of supramolecules. 10,11 From the pharmacokinetic point of view, thorough studies on the reaction mechanism with bio-related substances in aqueous solution are essential to grasp the chemical species and their transformations in vivo.…”
Section: Introductionmentioning
confidence: 99%